2022
DOI: 10.3390/pharmaceutics14061164
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing and Sonoporating Biofilm-Associated Bacteria with Sonobactericide

Abstract: Bacteria encased in a biofilm poses significant challenges to successful treatment, since both the immune system and antibiotics are ineffective. Sonobactericide, which uses ultrasound and microbubbles, is a potential new strategy for increasing antimicrobial effectiveness or directly killing bacteria. Several studies suggest that sonobactericide can lead to bacterial dispersion or sonoporation (i.e., cell membrane permeabilization); however, real-time observations distinguishing individual bacteria during and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Sonobactericide non-invasively removes IE biofilm using ultrasound-activated lipid-coated microbubbles [ 169 , 170 ]. Recent in vitro clinical studies have demonstrated the efficacy of microbubbles against IE-associated biofilm caused by Staphylococcus aureus by 84% degradation [ 171 ]. In a similar study, Kouijzer et al [ 172 ] demonstrated that vancomycin-decorated microbubbles are able to bind to the cell walls of gram-positive bacteria.…”
Section: Future Directionsmentioning
confidence: 99%
“…Sonobactericide non-invasively removes IE biofilm using ultrasound-activated lipid-coated microbubbles [ 169 , 170 ]. Recent in vitro clinical studies have demonstrated the efficacy of microbubbles against IE-associated biofilm caused by Staphylococcus aureus by 84% degradation [ 171 ]. In a similar study, Kouijzer et al [ 172 ] demonstrated that vancomycin-decorated microbubbles are able to bind to the cell walls of gram-positive bacteria.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another potential theranostic avenue for IE, called sonobactericide ( Lattwein et al, 2020 ), is focused on the removal of IE biofilms, non-invasively, using ultrasound-activated lipid-coated microbubbles (1–10 µm in diameter), clinically approved as ultrasound contrast agents. Non-targeted microbubbles exposed to focused and unfocused ultrasound have been shown to be effective against in vitro biofilms produced from clinical IE S. aureus isolates ( Lattwein et al, 2022 ). Ultrasound-induced microbubble displacement resulted in up to 84% biofilm degradation ( Lattwein et al, 2022 ), whereas the infected clot in vitro IE model mentioned previously in section 6.5 required the addition of thrombolytics to sonobactericide with an efficacy up to 97% ( Lattwein et al, 2018 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Non-targeted microbubbles exposed to focused and unfocused ultrasound have been shown to be effective against in vitro biofilms produced from clinical IE S. aureus isolates ( Lattwein et al, 2022 ). Ultrasound-induced microbubble displacement resulted in up to 84% biofilm degradation ( Lattwein et al, 2022 ), whereas the infected clot in vitro IE model mentioned previously in section 6.5 required the addition of thrombolytics to sonobactericide with an efficacy up to 97% ( Lattwein et al, 2018 ). Thrombolytics currently remain contraindicated for IE, however support exists for its use as a therapeutic agent ( Lerche et al, 2021 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Besides the ultrasound frequency and pressure, the driving pulse length is also a control parameter in sonoporation therapy. A wide range of pulse lengths have been employed to induce sonoporation, i.e., from a single pulse of a few acoustic cycles [11,20,37] to many repetitions of pulses containing thousands of cycles [38][39][40][41][42]. In in vitro sonoporation experiments on cell monolayer substrates, microbubbles driven by long ultrasound pulses will cluster due to the acoustic secondary radiation force [43].…”
Section: Introductionmentioning
confidence: 99%